Legal & regulatory framework for digital financial services in Kenya: A case for urgent reforms - Jackson Macharia Githu (Kenya Bankers Association (KBA), 2023)
This paper reviews the legal and regulatory framework governing digital financial services in Kenya including some of the unanswered questions by the current regulatory framework. The paper focusses on the question of the statutory definition of the rapidly evolving payment services, the architecture of the regulatory framework of the digital financial services and the regulation of digital credit providers. The paper identifies that there are risks and opportunities in the current regulatory framework and the regulatory regime should strike the required balance. The paper concludes by recommending that Parliament amends the definition of payment services in the National Payment Services Act. Further, even though the digital lenders regulatory framework has just come into force, the paper calls for its continued enhancement. The paper also calls for some minimum regulatory guidelines to be issued for the currently unregulated non digital lenders on areas such as interest rates and consumer protection. The paper also urges reconsideration of the regulatory framework to consolidate the regulators, laws and regulations on the area.
Keywords: 330